Estudo de dois dispositivos robóticos para reabilitação da marcha humana - Dechichi, Paulo Fernandes (2017)
In recent years, the robotic has been presented to improve the performance of repetitive motions and processes, being widely used in industry. Through its improvement, it was possible to develop robots to assist in the health area, such as the rehabilitation of patients with locomotion difficulties. The aim of the study is to analyze two mechanisms to be used by health professionals for the rehabilitation of the human gait. The first one is operated by cables and the second uses Parallel Mechanism. In order to achieve this objective, a brief review of the main robotic structures for the rehabilitation of human gait is presented, including the main characteristics of the normal human gait. To choose the best device it was initially presented the geometric modeling of each one and considering the platform motion equal to the human gait of a person of average Brazilian stature. It was studied the singularity configurations and the static modeling for each device. It was verified that the device which works with cables are not adequate for some movements due to singularities and untensioned cables in all platform configurations. After the second device verification and the model validation, the prototype scale was constructed to verify its kinematic functionality. An anthropometric wooden dummy was used, in scale, to replicate the human gait movement. Finally, the numerical results were compared to the prototype scale tests, considering angular variations of the joints and, as a result, it was possible to conclude that the Parallel Link Mechanism is feasible to replicate all desired movements.